THE EFFECT OF BIO ORGANIC FERTILIZER ON GROWTH OF PALM OIL (ELAEIS GUENEENSIS, JACK) SIX MONTHS AGE IN MAIN NURSERY - Ida Ketut Mudhita; Saprudin Saprudin; Muhamad Mundzir (Journal of Tropical Animal Science and Technology, 2020)
The purpose of this study to determine the effect of bio-organic fertilizer made from a mixture of cow dung, oil palm fiber and agricultural symbiotic microbes on the growth of oil palm seedlings. The research method uses four treatments: P0 (control): chemical fertilizer (CF) 100%, P1 (CF 100%+50% bio organic fertilizer/BOF, 100 kg/ha), P2 (CF100%+100% BOF, 200 kg/ha) and P3 (CF 100%+150% BOF, 300 kg/ha). The fertilizer was applied to oil palm seedlings aged six months in polybags each of 30 plants per treatment or a total of 120 plants, every month for four months. The parameters observed were: plant height, stem diameter, number of fronds and plant weight. Measurements were taken every month, except for the weight of the plants taken at the end of the study by taking a sample of plants in the amount of 10% from each treatment. The results showed that the addition of bio-organic fertilizer increased plant height 20.58% (from 108.23 to 130.5 cm) at P0, P1 by 25.21% (from 108.43 to 135.7 cm), P2 by 35.19% (108.73-147 cm) and the highest in P3 was 36.32% (108.66-148.12 cm). The stem diameter of oil palm plants increased by 34.47% (5.87-7.89 cm) in P0 (control) P1 by 33.11% (6.1-8.1 cm), P2 by 44.24% (5, 87-8.47 cm), and the highest in P3 was 48.66% (5.83-8.67 cm). The number of palm fronds increased by 19.03% (14.37-17.1) in P0 (control), P1 by 17.59% (14.4-17.77), P2 by 23.69% (14.36- 17.77) and the highest in P3 was 24.72% (15.1-18.83). The dry weight of oil palm plants aged 10 months at P0 596.6 g, P1 was 634.1 g, P2 was 742.9 g and the highest was at P3 762.6 g. The conclusion of this study that the addition of bio- organic fertilizer significantly affected the growth of oil palm seeds, the best dose economically in P2 that is an increase of 100% biofertilizer or 200 kg / ha. The conclusion of this study is that the addition of bio organic fertilizer has a significant effect on the growth of oil palm seedlings, with the best results on P3 (addition of 150% BOF), but the best dose economically on P2 is the addition of 100% BOF or 200 kg/ha, due to growth at P2 and P3 is not significantly different.